Free and unfettered? An American socialist on the elections in Poland. [With a] forew. by J.S. Middleton (Montgomeryshire Printing Co., 1947)
With appendix: Zulawski, Zygmunt, Two speeches in the New parliament in Warsaw on February 8th and 18th, 1947.